Intracellular dehydrogenation catalysis leads to reductive stress and immunosuppression - Jiang, Jie; Zheng, Huizhen; Wang, Zhenzhen; Wang, Xinlian; Xie, Qianqian; Liu, Xi; Yang, Qing; Cai, Xiaoming; Gao, Xingfa; Li, Ruibin; Chen, Chunying (Nature nanotechnology, 2025)
Imbalanced redox homeostasis, involving either oxidative stress or reductive stress, can profoundly impact cellular functions, contributing to various diseases. While the implications of oxidative stress in the adverse effects of nanoparticles have been extensively studied, our comprehension of reductive stress within the context of nano-redox system interactions remains limited. Here we illuminate a domino effect initiated by the dehydrogenase-like activity of transition metal borides. Specifically, seven transition metal borides were identified to emulate the enzymatic activity of natural dehydrogenases, resulting in heightened levels of reductive constituents within critical biological redox pairs in cells. Mass cytometry analysis provides compelling evidence that reductive stress initiates an immunosuppressive environment within lung tissues, promoting the metastasis of breast cancer cells to the lungs. In summary, our study unveils the chemical basis of nano-induced reductive stress and establishes a mechanistic axis that interlinks dehydrogenase-like activity, reductive stress, immunosuppression and tumour metastasis.
Keywords: Oxidative Stress; nádory plic; Lung Neoplasms; oxidační stres; Humans; Catalysis; oxidace-redukce; Female; lidé; zvířata; myši; Mice; Breast Neoplasms; ženské pohlaví; nádorové buněčné linie; nádory prsu; Oxidation-Reduction; Animals; Cell Line, Tumor; katalýza